2018
DOI: 10.1002/glia.23454
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic astrocyte activation evokes BOLD fMRI response with oxygen consumption without neuronal activity modulation

Abstract: Functional magnetic resonance imaging (fMRI) based on the blood oxygenation level-dependent (BOLD) signal has been used to infer sites of neuronal activation in the brain. A recent study demonstrated, however, unexpected BOLD signal generation without neuronal excitation, which led us to hypothesize the presence of another cellular source for BOLD signal generation. Collective assessment of optogenetic activation of astrocytes or neurons, fMRI in awake mice, electrophysiological measurements, and histochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 60 publications
2
70
0
Order By: Relevance
“…The early brain slice work of Zonta et al (), showing astrocyte regulate vessel diameter, was then followed by a first in vivo study demonstrating sensory‐evoked increases in astrocyte Ca 2+ during functional hyperemia (Takano et al, ). Today, while still somewhat controversial, both in vivo (Otsu et al, ; Takata et al, ; Zonta et al, ) and brain slice (Attwell et al, ; Mulligan & MacVicar, ; Takano et al, ; Zonta et al, ) evidence supports a role for astrocytes in the regulation of CBF following increases in neuronal activity, NVC. Moreover, alterations in basal astrocyte Ca 2+ levels, independent of those evoked by increases in neuronal activity, modulate vascular tone (Kim et al, ; Rosenegger, Tran, Wamsteeker Cusulin, & Gordon, ).…”
Section: Introductionmentioning
confidence: 99%
“…The early brain slice work of Zonta et al (), showing astrocyte regulate vessel diameter, was then followed by a first in vivo study demonstrating sensory‐evoked increases in astrocyte Ca 2+ during functional hyperemia (Takano et al, ). Today, while still somewhat controversial, both in vivo (Otsu et al, ; Takata et al, ; Zonta et al, ) and brain slice (Attwell et al, ; Mulligan & MacVicar, ; Takano et al, ; Zonta et al, ) evidence supports a role for astrocytes in the regulation of CBF following increases in neuronal activity, NVC. Moreover, alterations in basal astrocyte Ca 2+ levels, independent of those evoked by increases in neuronal activity, modulate vascular tone (Kim et al, ; Rosenegger, Tran, Wamsteeker Cusulin, & Gordon, ).…”
Section: Introductionmentioning
confidence: 99%
“…TGN-020 is known to increase astrocyte swelling, reduce water flow from astrocytes into the peri-capillary Virchow-Robin space, reduce peri-capillary fluid pressure and capillary lumen expansion and increase regional baseline CBF [34]. It has been suggested that astrocytes play a major role in neurovascular coupling [21]. Excitatory events can drive activity in interneurons [35] or astrocytes [36,37] that recruit a local hemodynamic response [38].…”
Section: Discussionmentioning
confidence: 99%
“…In another clinical study (Alshelh et al, 2018), regional alterations in T2 relaxation times have been speculated as indicative of astroglial activation in patients suffered of neuropathic pain. More recently, the origin of signal used by functional MRI to investigate large-group of neuronal activations has been debated, considering preclinical evidences that evoked astrocytic Ca 2+ waves can correlate with increased EEG power signal , astrocyte-evoked BOLD fluctuations (Takata et al, 2018), and transcranial direct current stimulation response (Monai and Hirase, 2018). These findings render furtherly more appealing the use of hybrid scanner that can acquire simultaneously PET, fMRI, and EEG signal (Mele et al, 2019).…”
Section: Pet and Mr Imaging Of Astrocytic Activationmentioning
confidence: 99%